Isolation of Trametes hirsuta La-7 with high laccase-productivity and its application in metabolism of 17β-estradiol. (August 2020) - Sun, Kai; Cheng, Xing; Yu, Jialin; Chen, Luojian; Wei, Jiajun; Chen, Wenjun; Wang, Jun; Li, Shunyao; Liu, Qingzhu; Si, Youbin
Abstract: Estrogens, which are extensive in the eco-environments, are a category of high-toxic emerging contaminants that induce metabolic disorders and even carcinogenic risks in wildlife and humans. Here we investigate whether fungus-secreted laccase can be used as a green catalyst to eliminate a representative estrogen, 17 β -estradiol (E2). A white-rot fungus Trametes hirsuta La-7 with high laccase-productivity, was isolated from pig manure-contaminated soil. Extracellular laccase activity expressed by strain La-7 was 65.4 U·mL −1 for a 3 d inoculation under the optimal fermentation parameters. The concentrated-crude laccase from Trametes hirsuta La-7 (CC- Th Lac) was capable of effectively metabolizing E2 at pH 4–6, and the apparent pseudo first-order reaction rate constant and half-life values were respectively 0.027–0.055 min −1 and 25.86–12.67 min ( R 2  > 0.98). The mass measurement of high-resolution mass spectrometry in combination with 13 C-isotope labeling identiﬁed that the main by-products of E2 metabolism were dimers, trimers, and tetramers, which are consistent with radical-driven C–C and/or C–O–C covalent coupling pathway, involving the initial enzymatic production of phenoxy radical intermediates and then the successive oxidative-oligomerization of radical intermediates. The formation of oligomers dramatically reduced the estrogenic activity of E2. Additionally, CC- Th Lac also exhibited high-efficiency metabolism capability toward E2 in the natural water and pig manure, with more than 94.4% and 91.0% of E2 having been metabolized, respectively. These findings provide a broad prospect for the clean biotechnological applications of Trametes hirsuta La-7 in estrogen-contaminated ecosystems. Graphical abstract: Image 1 Highlights: A Trametes hirsuta La-7 was isolated from contaminated soil to yield laccase. Activity of laccase reached 65.4 U·mL −1 under the optimal fermentation conditions. E2 metabolites were identified by HRMS combined with 13 C-isotope labeling. E2 was step-polymerized to produce various oligomers via radical coupling mechanism. CC- Th Lac was capable of effectively metabolizing E2 in environmental matrices.